Anti-IgE therapy for IgE-mediated allergic diseases: from neutralizing IgE antibodies to eliminating IgE(+) B cells - Hu, Jiayun (Clin Transl Allergy, 2018)
Allergic diseases are inflammatory disorders that involve many types of cells and factors, including allergens, immunoglobulin (Ig)E, mast cells, basophils, cytokines and soluble mediators. Among them, IgE plays a vital role in the development of acute allergic reactions and chronic inflammatory allergic diseases, making its control particularly important in the treatment of IgE-mediated allergic diseases. This review provides an overview of the current state of IgE targeted therapy development, focusing on three areas of translational research: IgE neutralization in blood; IgE-effector cell elimination; and IgE(+) B cell reduction. IgE-targeted medicines such as FDA approved drug Xolair (Omalizumab) represent a promising avenue for treating IgE-mediated allergic diseases given the pernicious role of IgE in disease progression. Additionally, targeted therapy for IgE-mediated allergic diseases may be advanced through cellular treatments, including the modification of effector cells.